Institutional Arrangements and Processes in Marine Fishery Reserves-Sanctuaries Establishment in Lagonoy Gulf - Bradecina, Raul G; Nieves, Plutomeo (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
Date submitted: April 18, 2006; Date accepted: September 13, 2006 This paper described the process and institutional arrangement of MFR-S in Lagonoy Gulf from period 1993 to 2004. The analysis made use of primary and secondary data mainly derived from key informant interviews and participatory resource assessment (PRA). Results showed that the establishment of Marine Fisheries Reserve-Sanctuary in Lagonoy Gulf started in 1993. During the ten-year period between 1993 and 2004, a total of 8 MFR-S were established with majority in Albay and the least in Camarines Sur. Two categories of institutional arrangements were identified in the gulf, namely: LGU-initiated and community-initiated, commonly facilitated by external agents during the project's incipient stage. Three types of institutional partnership emerged namely: Local Government Unit-Non-Government Organizations/ National Government Agencies (LGU-NGOs/NGAs) and people's organization (PO)-academe partnerships. The institutional arrangement and type of partnership determine the process and mechanism of implementation of MFR-S in Lagonoy Gulf. An academe-facilitated process focuses on research as starting point. NGO-facilitated process starts generally with community organizing, while NGA mostly proceed with policy implementation. The community-academe partnership is strong in the preparatory and planning phase. The LGU-NGO/NGA partnership on the other hand, is strong in the ordinance adoption phase. Some factors could derail or facilitate the development of the establishment process in the logical order, these are: the capability of the LGU, the agenda and the long-term commitment of external agents. The interplay of these hindering and facilitating factors in the establishment process of MFR-S developed a 3-phase logical establishment process model for Lagonoy Gulf consisting of the following phases: (1) preparation and planning; (2) ordinance approval; and (3) implementation and management. This typology evolved two distinct types of mechanism of implementation, namely: (i.) a mechanism where the MFR-S planning preempts the ordinance for its establishment; and (ii.). a mechanism where the MFR-S planning precedes the ordinance for its establishment. The former type of implementation mechanism featured an enactment of ordinance establishing the MFR-S followed by a community consultation and management planning. The scheme resulted to the non-integration of the MFR-S management plan into the ordinance that established it. While the latter type of implementation mechanism featured a community consultation and MFR-S establishment (barangay CRM) followed by the enactment of an ordinance establishing an MFR-S by the municipal government. The scheme resulted to the integration of the MFR-S management plan into the ordinance that established it. A more appropriate and effective MFR-S establishment process could be evolved from the Lagonoy Gulf experience by placing the different institutional relevant institutional arrangements and phase sequence could be developed from its MFR-S establishment experience arrangement and processes typologies at appropriate periods capitalizing on their respective strengths.